Absence of changes in GABA concentrations with age and gender in the human anterior cingulate cortex: a MEGA-PRESS study with symmetric editing pulse frequencies for macromolecule suppression - Aufhaus, Eva; Meyer-Lindenberg, Andreas; Ende, Gabriele (Magnetic resonance in medicine, 2013)
Despite MEGA-PRESS being a robust method for editing the GABA resonance, there are macromolecule resonances at the same chemical shift that are coedited with this sequence. Although this is a known problem, it is still often overlooked. We aimed to evaluate the amount of macromolecule signal coedited, as well as the gender and age dependencies for the GABA resonance at 3.01 ppm using MEGA-PRESS with two different editing pulse frequencies. Forty-five healthy subjects (21-52 years) were included in an in vivo single voxel MEGA-PRESS study at 3.0 T. Phantom measurements were conducted to measure the signal loss when switching the editing pulse between 1.5 and 1.9 ppm instead of the mostly used switching between 1.9 and 7.5 ppm. The in vivo GABA signal detected by switching the editing pulse frequencies between 1.5 and 1.9 ppm was only 50% of the mean GABA detected by switching the editing pulse frequencies between 1.9 and 7.5 ppm. No gender differences were detected. A small age dependency was observed for GABA plus macromolecules, but not for GABA, suggesting an age-dependent macromolecule increase.